Northern Goshawk and Golden Eagle ighting details contributed by Bob Cecil, spring 1991 - Cecil, Robert I.et al (1991)
Field notes written by Bob Cecil detailing the sighting of a Northern Goshawk at Shimek State Forest, Croton Unit and the sighting of a Golden Eagle at Lacey-Keosauqua State Park. Epson - sheet feed